Prinsip Good Corporate Governance Bank Dalam Mendukung Indonesia Emas 2045 - Sukarno, Karmila Sari; Nurviana, Reky (Sharia Journal and Education Center Publishing, 2024)
Abstract In order to support Indonesia Emas 2045 agenda, it is crucial to implement Good Corporate Governance (GCG) principles in banking. This includes ensuring that banks operate efficiently, fairly, and in compliance with all applicable laws and regulations. Effective GCG can help prevent financial mismanagement, promote public trust, and support sustainable economic development. However, the banking sector has faced significant challenges, including the BLBI and Century Bank crises, which highlight the need for robust GCG practices. These crises underscore the importance of transparent and accountable banking practices to ensure public trust and prevent future financial mismanagement. Indonesia's economic development is crucial for achieving its national vision, Indonesia Emas 2045. Good Corporate Governance (GCG) is essential for the health and stability of the banking sector, ensuring transparency, accountability, responsibility, independence, and fairness. Keywords: Bank, Good Corporate Governance, Indonesia Emas 2045 Abstrak Dalam rangka mendukung Indonesia Emas 2045, diperlukan penerapan prinsip-prinsip Good Corporate Governance (GCG) di sektor perbankan. Ini termasuk memastikan bank beroperasi secara efisien, adil, dan sesuai dengan semua peraturan yang berlaku. GCG yang efektif dapat membantu mencegah manajemen keuangan yang tidak tepat, mempromosikan kepercayaan publik, dan mendukung pembangunan ekonomi yang berkelanjutan. Namun, sektor perbankan telah menghadapi tantangan yang signifikan, termasuk krisis BLBI dan Century Bank, yang menunjukkan perlunya praktik GCG yang kuat. Krisis-krisis ini menegaskan pentingnya praktik perbankan yang transparan dan bertanggung jawab untuk mempertahankan kepercayaan publik dan mencegah manajemen keuangan yang tidak tepat di masa depan. Pembangunan ekonomi Indonesia sangat penting untuk mencapai visi nasional, Indonesia Emas 2045. GCG adalah esensial untuk kesehatan dan stabilisasi sektor perbankan, memastikan transparansi, tanggung jawab, kewajiban, independensi, dan keadilan. Kata Kunci: Bank, Good Corporate Governance, Indonesia Emas 2045